RANCANG BANGUN SISTEM INFORMASI PEMESANAN TIKET BUS BERBASIS WEB PADA PO. SARI HARUM - Cecep Abdul Rahman; Dwi Robiul Rochmawati (POLITEKNIK PIKSI GANESHA, 2019)
This research aims to build information systems of booking bus tickets at PO. Sari Harum, find the problem and find solutions to these problem. Currently booking tickets at PO. Sari Harum still use manual systems. The unavailability of a database for storing the data the customer tickets can be causes the loss of the archives. The research method used is to do research into the place of observation, interview and review of the literature. The concept of the design of this information system is to use object-oriented modeling approach with UML (Unified Modelling Language) and implemented by web applications as well as the PHP programming language. While software development method that is used is the Waterfall and using MySQL database. The application of bus ticket booking information system is so important to help the operational service of the customer in particular on ticket booking.